Interdependence of sequential cytotoxic T lymphocyte and natural killer cell cytotoxicity against melanoma cells. (3rd November 2022) - Friedmann, Kim S.; Kaschek, Lea; Knörck, Arne; Cappello, Sabrina; Lünsmann, Niklas; Küchler, Nadja; Hoxha, Cora; Schäfer, Gertrud; Iden, Sandra; Bogeski, Ivan; Kummerow, Carsten; Schwarz, Eva C.; et al.
Abstract : Abstract: Cytotoxic T lymphocytes (CTL) and natural killer (NK) cells recognize and eliminate cancer cells. However, immune evasion, downregulation of immune function by the tumour microenvironment and resistance of cancer cells are major problems. Although CTL and NK cells are both important to eliminate cancer, most studies address them individually. We quantified sequential primary human CTL and NK cell cytotoxicity against the melanoma cell line SK‐Mel‐5. At high effector‐to‐target ratios, NK cells or melan‐A (MART‐1)‐specific CTL eliminated all SK‐Mel‐5 cells within 24 h, indicating that SK‐Mel‐5 cells are not resistant initially. However, at lower effector‐to‐target ratios, which resemble numbers of the immune contexture in human cancer, a substantial number of SK‐Mel‐5 cells survived. Pre‐exposure to CTL induced resistance in surviving SK‐Mel‐5 cells to subsequent CTL or NK cell cytotoxicity, and pre‐exposure to NK cells induced resistance in surviving SK‐Mel‐5 cells to NK cells. Higher human leucocyte antigen class I expression or interleukin‐6 levels were correlated with resistance to NK cells, whereas reduction in MART‐1 antigen expression was correlated with reduced CTL cytotoxicity. The CTL cytotoxicity was rescued beyond control levels by exogenous MART‐1 antigen. In contrast to the other three combinations, CTL cytotoxicity against SK‐Mel‐5 cells was enhanced following NK cell pre‐exposure. Our assay allows quantification of sequential CTL and NK cell cytotoxicity and might guide strategies for efficient CTL–NK cell anti‐melanoma therapies. Key points: Cytotoxic T lymphocytes (CTL) and natural killer (NK) cells eliminate cancer cells. Both CTL and NK cells attack the same targets, but most studies address them individually. In a sequential cytotoxicity model, the interdependence of antigen‐specific CTL and NK cell cytotoxicity against melanoma is quantified. High numbers of antigen‐specific CTL and NK cells eliminate all melanoma cells. However, lower numbers induce resistance if secondary CTL or NK cell exposure follows initial CTL exposure or if secondary NK cell exposure follows initial NK cell exposure. On the contrary, if secondary CTL exposure follows initial NK cell exposure, cytotoxicity is enhanced. Alterations in human leucocyte antigen class I expression and interleukin‐6 levels are correlated with resistance to NK cells, whereas a reduction in antigen expression is correlated with reduced CTL cytotoxicity; CTL cytotoxicity is rescued beyond control levels by exogenous antigen. This assay and the results on interdependencies will help us to understand and optimize immune therapies against cancer. Abstract : Abstract figure legend Cytotoxic T lymphocytes (CTL) and natural killer (NK) cells eliminate cancer cells. At high killer‐to‐cancer cell ratios (left row), CTL or NK cells eliminate all melanoma cells, indicating that melanoma cells are initially not resistant to either CTL‐ or NK cell‐mediated cytotoxicity. At low killer‐to‐cancer cell ratios, CTL or NK cells do not eliminate all melanoma cells (middle row). Sequential second exposure of melanoma cell survivors to fresh CTL or NK cells reveals that pre‐exposed melanoma cells are usually not eliminated as efficiently as non‐exposed melanoma cells, indicating that pre‐exposed melanoma cells acquire resistance to killer cells (right row). Only if secondary CTL exposure follows initial NK cell exposure is cytotoxicity not reduced but, on the contrary, even enhanced.